Three-Dimensional Analysis on Thermal Stresses in A Perforated Disc Brake of Vehicle - Lee, Jin Ming (Universiti Teknologi Petronas, 2010)
This report provides background information on small vehicle‟s perforated disc brake which is subjected to high frictional force during braking. This frictional action will consequently converts the car‟s kinetic energy into thermal energy in order to slow the car down. On the other hand, the thermal energy will be the source of thermal stresses in the perforated disc brake. The objectives of this project are to analyze and simulate three dimensional temperature and thermal stresses distribution within the perforated disc brake and to analyze the effect of having perforated holes by comparing the results with a non-perforated disc brake. The methodologies used in achieving these objectives are through numerical calculation and finite elements analysis by ANSYS. The temperature distributions obtain from the simulation show that maximum temperature produced by perforated and non perforated disc brakes is almost the same but perforated holes in perforated disc brake contributed to better temperature distribution within its cross section, giving better cooling effect. While for the thermal stress distribution, the generated Von Mises stress for perforated disc brake is lower than non perforated disc brake but high magnitude of Von Mises stress exists around the perforated holes. Furthermore, overall top surface Von Mises stress distribution shows that perforated disc brake has better stress distribution with extra lower stress region. Thus, it can be concluded through this project that perforated disc brake is better in increasing the performance of vehicle but the weighting are between high stress concentration at the perforated zones and better cooling ability as compared to conventional disc brake.